Enhancing motivation and effectiveness in Chinese language learning through calligraphy instruction: a community-based study - Chan, Jie Yan; Zakaria, Muhamad Zaidi; Mohamad Aris, Nurbaya; Amat Suparia, Fariz Azzuan (Universiti Teknologi MARA, Kedah, 2024)
Research has consistently highlighted the complexity of learning Chinese characters as one of the most challenging aspects of acquiring the Chinese language (Shen, 2005; Huang & Ma, 2007). However, recent studies indicate that cultural instruction may enhance learners' motivation in Chinese (Wen, 2011; He & Liu, 2024). This study investigates two primary objectives: 1) Chinese calligraphy instruction can augment learners' motivation in studying Chinese, and 2) the impact of calligraphy instruction on the effectiveness of Chinese language acquisition. A one-hour calligraphy workshop had been implemented at an orphanage in Malacca, where participants engaged in writing and learning 24 Chinese characters. The study sample comprised 25 orphans aged 8 to 18 with no prior background in Chinese. The level of motivation in calligraphy and Chinese characters was assessed through observations of students' engagement during the writing process and their sustained interest over time. The effectiveness of character learning was evaluated based on students' abilities in writing, memory retention, and reading proficiency. Data were analyzed using thematic analysis. The results indicate that Chinese calligraphy instruction significantly enhances students' motivation in learning Chinese and improves their language acquisition effectiveness.